Erodium hakangurii (Geraniaceae), a new species from inner Anatolia (Turkey) - Özüdoğru, Bariş; Özgi̇şi̇ Kurtuluş (Phytotaxa, 2025)
Erodium hakanguriii, from the Altınyayla district of Sivas Province in the eastern part of inner Anatolia (Turkey) is described as a new species based on morphological evidence. It resembles E. sibthorpianum from the calcareous areas of north-west Anatolia, but can be distinguished by several morphological characteristics including longer stems, leaf blades, beak of fruits, and the number of peduncles in each stem. Diagnostic morphological characters, a full description, a revised key to the Absinthoides species group in Turkey, as well as pollen and seed micrographs are provided. Furthermore, the IUCN Red List category of the new species is assessed as Critically Endangered (CR) due to its limited distribution and agricultural pressure.